Healthcare cost consciousness among physicians and their attitudes towards controlling costs in Jordan: a cross sectional study - Mohmmed Hasan Yasin; Abdallah Y. Naser (BMC, 2022)
Abstract Background One of the most significant factors influencing medication adherence and, ultimately, therapeutic outcomes for patients is the cost. The aim of this study was to examine the cost-containment strategies used by physicians in Jordan while focusing on the importance of cost consciousness in addressing healthcare costs and its consequences. Method A quantitative study was conducted between June 19 and November 15, 2021, through a cross-sectional survey using a self-administered questionnaire. Results A total of 389 physicians participated in this study. Governments (65.6%), health insurance companies (60.2%), and pharmaceutical and device manufacturers (57.9%) were the most frequently mentioned entities as being primarily responsible for reducing healthcare costs. Participating physicians showed a high level of enthusiasm towards all domains of reducing healthcare costs with a mean percentage of 88.3% (standard deviation (SD): 0.04). When discussing physicians' roles in containing healthcare costs and the effects of cost-conscious practice, most respondents agreed that there is currently too much emphasis on test and procedure costs (83.0%), that decision support tools that show costs would be helpful in their practice (84.5%), and that physicians need to take a more prominent role in limiting the use of unnecessary tests (86.0%). Around 70.0% of physicians agreed that they requested more tests when they did not know the patient well, and 80.0% of them stated that they considered the uncertainty involved in patient care to be disconcerting. Conclusion Participating physicians showed a moderate level of cost consciousness in Jordan. However, this must be higher because it will eventually lead to cost-related nonadherence, which will have a negative impact on the patient's health.